EFISIENSI PENGGUNAAN WAKTU PENGISIAN OVERBURDEN KE DUMP TRUK PADA PT. PAMA PERSADA NUSANTARA DISTRIK BAYA KUTAI KERTANEGARA - -, Sugiarto - (EKONOMIA, 2014)
The development of today's economy continued to progress. Economic progress is followed by many companies that grow and evolve with the growing needs, the progress of time and technology. The number of companies that develop new technologies and moving in the same field, making the company should be able to create new innovations and efficiency in order to compete in a business world that is increasingly tight. With the national and global economic situation that has not improved and was no doubt, with this condition have a significant impact on the developments and progress of the company. Basically every company in the operations, experiencing the problems associated with the planning, operation time, production costs and much more. Thus the company is required to be able to carry out efficiency.The purpose of this study was to determine whether the use of the level of charging time to overburden dump truck at PT. Pamapersada already efficient.The analytical tool used to conduct this research is System Configuration Single Phase Single Channel (Single Channel Single Phase) which is an approach to the calculation of the efficiency of the queuing time to calculate lost time when the queue fills overburden dump truck to take place. In this calculation, the value of Î» = 19 units / hour, and Î¼ = 22 dump trucks based research service number every hour on the front loading of the equations that have been presented, to find the value of busyness level system (Ï) values obtained 86% level of activity system for serve 19 dump trucks and dump trucks no probability in the system by 14% or 8.4 minutes, which means that in the calculation of the number of arrivals this study only 19 dump trucks / hour is not efficient, because there is still a void in the system by 14% or 8.4 min / h, with normal charging time to the overburden dump truck for 3 minutes. With a time of 8.4 minutes in the production process to fill the EX 2000 can overburden into dump truck dump truck as much as 2.8 / hr, equivalent to 117.6 BCM, and known to the average dump truck in the service process is only 0.83 units , this value is changed and is flaktuatip, while the time taken by each dump truck or the average service time (service time) in the process of service is 2.3 minutes.